Long‐term survival with low toxicity after allogeneic transplantation for acute myeloid leukaemia and myelodysplasia using non‐myeloablative conditioning without T cell depletion. (29th May 2013) - Davies, Jeff K.; Taussig, David; Oakervee, Heather; Smith, Matthew; Agrawal, Samir; Cavenagh, Jamie D.; Gribben, John G.
Summary The toxicity burden and long‐term anti‐leukaemic effect of non‐myeloablative (NMA) allogeneic haematopoietic stem‐cell transplantation (AHSCT) for acute myeloid leukaemia (AML) and myelodysplasia (MDS) remains undefined. We report the outcome of 56 patients with AML/MDS transplanted from human leucocyte antigen‐matched donors using NMA conditioning without T‐cell depletion. With a median follow‐up of 5 years, treatment‐related mortality was 9% and current disease‐free survival (CDFS) was 45% (overall) and 55% (patients transplanted in remission). Development of graft‐versus‐host disease upon withdrawal of post‐transplant immunosuppression was associated with less relapse and better CDFS. These data confirm that NMA AHSCT without T‐cell depletion is safe and can result in sustained remissions of AML/MDS.